2010
DOI: 10.1258/la.2009.009042
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of α2-macroglobulin and α1-acid glycoprotein in rats subjected to repeated acute inflammatory stimulation

Abstract: The kinetics of a 2 -macroglobulin (a2M) and a 1 -acid glycoprotein (AAG) in rats repeatedly stimulated with intramuscular injections of turpentine oil at doses 0.05 and 0.4 mL/rat were investigated. Mean serum levels of a2M peaked at 48 h after the first turpentine oil injection, reaching 1.74 and 2.36 mg/mL at 0.05 and 0.4 mL/rat, respectively. AAG peaks were also observed at 48 h after injection, and the mean values were 2.02 and 2.53 mg/mL, respectively. These peak values of a2M and AAG differed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Jinbo et al measured the changes of many cytokines in rats injected with turpentine oil and found that only interleukin-6 (IL-6) and cytokine-induced neutrophil chemoattractant-1 (CINC-1) increase prior to the elevation of α2M serum levels [17]. IL-6 and CINC-1 levels also increase prior to elevation of α 1 -acid glycoprotein levels in rats stimulated by either injection of turpentine oil or inoculation with Staphylococcus aureus [12]. Therefore, IL-6 and CINC-1 are presumed to contribute to the production of acute phase proteins during the inflammatory response.…”
mentioning
confidence: 99%
“…Jinbo et al measured the changes of many cytokines in rats injected with turpentine oil and found that only interleukin-6 (IL-6) and cytokine-induced neutrophil chemoattractant-1 (CINC-1) increase prior to the elevation of α2M serum levels [17]. IL-6 and CINC-1 levels also increase prior to elevation of α 1 -acid glycoprotein levels in rats stimulated by either injection of turpentine oil or inoculation with Staphylococcus aureus [12]. Therefore, IL-6 and CINC-1 are presumed to contribute to the production of acute phase proteins during the inflammatory response.…”
mentioning
confidence: 99%
“…Turpentine oil is known to induce acute inflammation and has been used to induce acute inflammation in rats and dogs [1,3,6,8,9,12]. in this study, turpentine oil (Wako Pure Chemical industries, Ltd.) was thus used to induce acute inflammation by intramuscular injection at 1.0 ml/kg body weight at 2 days after the end of acetaminophen or CCl 4 administration.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Serum concentrations of α2M were measured by an enzyme-linked immunosorbent assay (eLisa) according to the procedure described by Honjo et al [8].…”
Section: Measurement Of Serum Concentrations Of α2mmentioning
confidence: 99%
See 2 more Smart Citations